PRODUKTIVITAS DAN BEBAN KERJA OPERATOR GERGAJI RANTAI, PADA KEGIATAN PENEBANGAN POHON BERBANIR TINGGI DI HUTAN ALAM DI KALIMANTAN TENGAH - Maraan Mansyur Idris; Soenamo Soenamo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
In general, there are three basic types/methods of chain saw operator's body position in doing mechanical tree felling in natural forest i.e; felling with squat, felling with standing in deeply bending forward and standing while both arms in extreme position in the soulder joint. However, the body Position of chain saw operator in high buttress tree felling are usually in standing while both arms in extreme position in the shoulder joint.The extreme body position above does not only generate static muscular load cauaing early fatique and pain in the shoulder joint (Hagberg, et al, 1987) but also cause physiological load during work (Ayaz,.1987). For this matter, a study was conducted for the improvement of worker's productivity and workstress by introducing a new methbd of body position's felling technique.The investigation took place at Central Kalimantan in 1989. The results of this research as follows:1.From faal variable point of view, the chain saw operator's workstress during work is higher than the limited works-tress level recommended by international medical opinion.2.New felling technique applied on high buttress tree of 150 to 300 cm can reduse workstress rate about 3-8 beats/min. While, if it is applied on high buttress tree of > 300 cm causes the operator chain saw's workstres about 1-4 beats/min lower than operator chain saw's workstress. in felling of tree with conventional method.3.Productivity rote with new felling method applied on buttrea high of 150 cm - 300 cm and > 300 cm are about 19.298rm3/hr and 18.207 m3/hr. The productivity rate with conventional method applied on high buttress of 15’0 cm -300 and> 300 cm are 22.974 m3/hr and 24.974 m.3/hr.4.Altliough the use of new method on high buttrea tree felling causes negative effect in work productivity but in fact it can increasethe forest wood utilization.about 2.63% -4.27%.